1960
DOI: 10.1063/1.1700888
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Surface Degradation of Polymethylmethacrylate

Abstract: The surface degradation of both linear and crosslinked polymethylmethacrylate (PMM) has been studied over the surface temperature range of 550° to 910°K by means of a hot-plate pyrolysis technique. It was demonstrated that surface gasification due to the high heat flux at the decomposing PMM surface involves a depolymerization process and surface desorption of methylmethacrylate monomer. The apparent activation energy for the linear rate of regression of the solid PMM surface (linear pyrolysis rate) was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1961
1961
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Of particular importance to this discussion is the fact that the rate controlling mechanism of surface decomposition of certain solids has been found experimentally to be different from that of decomposition in the bulk phase under isothermal conditions. This duality of thermal decomposition has been demonstrated with ammonium nitrate (11) and typical polymeric binders (8,12), where it was shown that at high surface temperatures endothermic surface vaporization or dissociative sublimation is apparently rate determining. The duality of the reaction mechanism (bulk and surface) in ammonium nitrate is related to the manner in which thermal energy is supplied to the solid.…”
Section: Grain Burningmentioning
confidence: 92%
“…Of particular importance to this discussion is the fact that the rate controlling mechanism of surface decomposition of certain solids has been found experimentally to be different from that of decomposition in the bulk phase under isothermal conditions. This duality of thermal decomposition has been demonstrated with ammonium nitrate (11) and typical polymeric binders (8,12), where it was shown that at high surface temperatures endothermic surface vaporization or dissociative sublimation is apparently rate determining. The duality of the reaction mechanism (bulk and surface) in ammonium nitrate is related to the manner in which thermal energy is supplied to the solid.…”
Section: Grain Burningmentioning
confidence: 92%
“…However, such assumptions might not hold. Previous works showed [39] that for surface temperatures below 714 K (typical PMMA burning surface temperatures are about 650 K), the polymer surface is not saturated with monomer. The formation of monomers and diffusion to the surface are the rate-controlling processes of gasification.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal decomposition of PMMA involves a depolymerization and desorption of MMA towards the evolved gas-phase plume. The mechanism for PMMA surface degradation according to Chaiken et al [43] occurs in three stages with: (a) monomer forming near the surface, (b) diffusion of monomer to the surface, and (c) desorption of the monomer from the surface. Zeroth and first-order kinetics have been considered for the thermal decomposition of PMMA, effective activation energies for the desorption of MMA have been reported between 29 and 84 kJ/mol [6,43,44].…”
Section: Kineticsmentioning
confidence: 99%
“…Zeroth and first-order kinetics have been considered for the thermal decomposition of PMMA, effective activation energies for the desorption of MMA have been reported between 29 and 84 kJ/mol [6,43,44]. Chaiken et al [43] reported activation energies for: desorption (E ds ) of MMA from the polymer, chain propagation (E p ), chain depropagation (E d ), and diffusion of monomer (E D ) in the polymer with respective values of 46, 23, 89 and 145 kJ/mol. Fig.…”
Section: Kineticsmentioning
confidence: 99%